Youth, ethnicity, and a 'reverse digital divide': a study of Internet use in a divided country - Milioni, Dimitra L.; Doudaki, Vaia; Demertzis, Nicolas (My University, 2014)
Internet use among young people in multicultural societies is differentiated according to socioeconomic and cultural factors, one of which is their ethnic background. This study is concerned with the unreported case of Cyprus – the last divided country in Europe, with most Greek Cypriots living in the south and most Turkish Cypriots living in the northern part of the island. The study explores two main questions: First, are online experiences of young people in Cyprus shaped by socioeconomic factors, such as gender, education, and income? Second, is ethnicity a defining factor regarding the kinds of activities young people undertake online? Analysis of data obtained by a representative sample survey of about 350 young adult Cypriots aged 18–24 in both communities suggests the existence of a ‘reverse digital divide’, as the more disadvantaged community engages more often in expression, association, and learning online. This finding provides support for the diversification hypothesis that suggests a compensatory or remedial use of the Internet by disadvantaged youths.
Keywords: Cyprus; Ethnicity; Internet use; Reverse digital divide; Youth